The Implementation Cooperative Learning Model Course Review Horay (CRH) type to Improvement Of Student’s Mathematical Problem-Solving Ability - Nur Ismiyati; Kezia Priskilla Manullang (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2020)
This research is a kind of classroom action research. The purpose of this research is to know the improvement of student’s mathematical problem-solving ability by implementing cooperative learning model Course Review Horay (CRH) type at the twelve science 5 of SMA Negeri 2 Balikpapan academic year 2019/2020 for mathematic’s subject is trigonometric function derivatives. This research used Kemmis & McTaggart’s. This research also used test, observation, and  documentation for collecting the data. The result of this research showed that 1) there was improvement classically on student’s result that the mean of student’s result on  pre-cycle are 53,51 and then in the first cycle the mean of student’s result increased of 20,95 from pre cycle to 74,46; and then in the second cycle, that mean increased again of 10,31 from the first cycle to 84,77. 2) there was improvement on the percentages of stundent’s mathematical problem solving ability, which on pre-cycle the percentage was 46,75% then in the first cycle increased of 17 % from pre cycle to 63,73% and then in the second cycle, the percentage increased again of 22,5% from the first cycle to 86,25%. Based on those results,the conclusion  of this research is the implementing of cooperative learning model Course Review Horay (CRH) type could improving the student’s mathematical problem solving ability at  the twelve science 5 of SMA Negeri 2 Balikpapan academic year 2019/2020